1952
DOI: 10.1104/pp.27.3.475
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Gradual and Abrupt Changes in Root Temperature on Water Absorption

Abstract: IntroductionThe effects of low root temperature on various plant processes have long been known and extensively studied. It is generally recognized that one of its important effects is the reduction in water absorption of the plant; and the nearer the root temperature approaches the freezing point of water, the greater this effect will be manifested. The change in physical state, particularly the increase in viscosity with the decrease in temperature, of both water and protoplasm are undoubtedly two basic fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
1

Year Published

1955
1955
1975
1975

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 6 publications
(12 reference statements)
2
7
1
Order By: Relevance
“…The observation that no reduction in the rates of photosynthesis or transpiration occurred in Sitka spruce until the soil temperature was below 10C contrasts with many previous studies on other species (Kramer 1940(Kramer , 1942Kozlowski 1943;Bohning & Lusanandana 1952;Abdel Rahman, Kuiper & Bierhuizen 1959;Brouwer 1961;Ehrler 1963;Kuiper 1964;Cox & Boersma 1967;Babalola et al 1968;Benecke 1971;Havranek 1972;Rutland & Pallas 1972;Janes 1973), but is in agreement with two recent studies in which no reduction in photosynthesis or transpiration was observed at soil temperatures of 3YC, or above, in Scots pine and Norway spruce (Linder 1973) and in a diverse range of species of vascular plants (Anderson & McNaughton 1973). Differences amongst species have been interpreted as showing that the permeability of the roots is reduced to different extents by low temperature (Kramer 1969).…”
Section: Discussioncontrasting
confidence: 79%
“…The observation that no reduction in the rates of photosynthesis or transpiration occurred in Sitka spruce until the soil temperature was below 10C contrasts with many previous studies on other species (Kramer 1940(Kramer , 1942Kozlowski 1943;Bohning & Lusanandana 1952;Abdel Rahman, Kuiper & Bierhuizen 1959;Brouwer 1961;Ehrler 1963;Kuiper 1964;Cox & Boersma 1967;Babalola et al 1968;Benecke 1971;Havranek 1972;Rutland & Pallas 1972;Janes 1973), but is in agreement with two recent studies in which no reduction in photosynthesis or transpiration was observed at soil temperatures of 3YC, or above, in Scots pine and Norway spruce (Linder 1973) and in a diverse range of species of vascular plants (Anderson & McNaughton 1973). Differences amongst species have been interpreted as showing that the permeability of the roots is reduced to different extents by low temperature (Kramer 1969).…”
Section: Discussioncontrasting
confidence: 79%
“…Doring's (1935) is the only previous report of species showing no reduction in water transport at very low root temperatures. Kramer (1940Kramer ( , 1942, Kozlowski (1943), Bohning andLusanandana (1952), Abd El Rahman et al (1959), Kuiper (1964), and Cox and Boersma ( 1967) reported decreases in transpiration accompanying decreases in root temperature in several plant species. These studies suggest a greater effect of low soil temperature upon transpiration than was found in the present investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of previous studies dealing with water transport at low root temperatures have been conducted with hydroponic-grown plants (Doring 1935, Kramer 1940, Bohning and Lusanandana 1952, Abd El Rahman et al 1959, Kuiper 1964 * * Significant at P < 0.01 *** Significant at P < 0.001 Brouwer 1965, Cox andBoersma 1967). This technique virtually eliminates temperature gradients in the root medium.…”
Section: Hydroponic Controlsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, another factor may be involved. Low temperature at the lower soil depths may be limiting water absorption in two ways: ( 1) by retarding root growth, and ( 2) by directly depressing water transport through roots. The process of water absorption has physiological temperature limits, and plant species vary in their range of tolerance to adverse root temperatures.…”
mentioning
confidence: 99%